The Role of The New Teachers Program in Enabling Kindergarten Teachers to Use Modern Teaching Strategies in Public Schools in Ajloun Governorate from Their Point of View - Abo Abeeleh, Tamather Abdalrahman Ahmad (Journal of Educational and Psychological Sciences, 2022)
This Study aimed to identify the role of the new teachers program in enabling kindergarten teachers to use modern teaching strategies in public schools in Ajloun governorate from their point of view, the researcher used the Descriptive approaches, study Sample consisted of (73) female teacher chosen intentionally, a questioner used as a tool to collect the data, which consisted (22) items, distributed to four fields the result of SPSS analysis shown that the role of the new teachers program in enabling kindergarten teachers to use modern teaching strategies in public schools in Ajloun governorate from their point of view was High with average (3.68 out of 5), The finding also showed there is statistically significant differences at (α≤0.05) refers to teachers years of experience in favor of 96 years and less) in addition there were statistically significant differences refers to teachers qualification in favor of Higher education. Based on the results, the researcher made a number of recommendations in addition to a proposal for complementary studies on the subject.